Development and Validation of a Three-Tier Test for Identifying Misconceptions in Organic Chemistry Course - Febliza, Asyti; Asep Kadarohman; Siti Aisyah; Norazilawati Abdullah (Journal of Innovative Science Education, 2024)
Misconceptions about organic chemistry topics still exist among university students. Identifying these misconceptions requires appropriate instruments. This study aims to develop and validate a three-tier test instrument for identifying misconceptions in organic chemistry lectures. The topics covered in the test include alkenes, alkynes, aromatic compounds, alkyl halides, alcohols, and ethers. This research follows a design and development approach, specifically adopting a product and tool research type with a focus on tool development & use, where validity is a research design concern. A total of 42 three-tier items were developed, combining multiple-choice questions with open reasoning and Certainty of Response Index (CRI) technique for confidence level assessment using a scale of 0, 1, 2, 3, 4, and 5. The content validity test by three expert judgments showed an average I-CVI of 0.98, with an average item proportion of 0.98. These results showed test item were valid. The test items were piloted with 25 students to examine empirical validity, resulting in 40 valid items and 2 invalid items. The Cronbach's Alpha reliability test yielded a value of 0.953, indicating very high reliability for the three-tier test instrument. Therefore, the three-tier test instrument can be used effectively to collect data and detect student misconceptions in organic chemistry lectures.